Analysis of Tax Obligations Under Article 21/ 26 and Potential Sanctions for PT NPA - Nur Amialia Putri; Syaifuddin AS; Danang Djoko Susilo; Dariansyah, Deddy (International Journal of Law Social Sciences and Management, 2025)
In the economic world, tax is one of the sources of state revenue that has an important role to finance budgets related to development and state interests. As the largest source of state revenue, taxes function to finance state expenditures both routine and development expenditures. So to increase tax revenue, the government carries out policies in the form of intensification and extensification which aim to secure and optimize tax revenue. The purpose of this study is to determine whether the implementation of the calculation, withholding, depositing, and reporting of Income Tax Article 21/26 along with potential sanctions carried out by PT.NPA is in accordance with applicable tax provisions, as well as knowing the obstacles faced and solutions to these obstacles. The method used in this research is with data collection techniques, namely literature (library research), conducting direct observations and interviews with employees in the taxation department of PT.NPA to collect data related to the research. Then the data obtained is processed with data processing techniques, namely descriptive and analysis. The conclusion drawn from this research is that the calculation and deduction of Income Tax Article 21/26 and the potential sanctions carried out by PT.NPA are in accordance with the provisions of the applicable Tax Legislation. The obstacles faced by PT NPA in the calculation and deduction, depositing, reporting of Income Tax Article 21 as a whole there are no obstacles and are in accordance with the regulations of the Director General of Taxes Number PER-16 / PJ / 2016. However, human resources who are less competent in understanding the latest tax regulations can cause the tax reporting process to take longer, so that reporting is close to due date.